Synthesis, X-Ray Crystal Structure, Bactericidal and Kinetic Study of some Mononuclear Zinc and Mercury Complexes Supported by Bisaroylhydrazone Derivatives - Kazem, Refaa Burhan; Al-Karawi, Ahmed Jasim M (Al-Nahrain Journal of Science, 2019)
This work includes the synthesis of two derivatives of cyclohexane bisaroylhydrazone: (L1) and (L2). These compounds were synthesized via the condensation reaction of 1,2-cyclohexanedione with an appropriate hydrazide derivative in acidic medium. The prepared ligands were reacted with zinc chloride or mercury chloride under ambient conditions. Consequently, mononuclear type complexes: [Zn(L1)Cl2] (1), [Zn(L2)Cl2].CH3CN (2). [Hg(L1)Cl2] (3) and [Hg(L2)Cl2].CH3CN (4) were obtained. Different techniques have been used to characterize the prepared organic ligands and their metal complexes (X-ray single crystal crystallography and microelemental analyses in addition to infrared, nuclear magnetic resonance, X-ray powder diffraction, Ultraviolate-visible-Near infrared, and mass spectroscopes). Depending upon the X-ray crystallography, it seems that the obtained products of 1, 2, 3 and 4 are mononuclear complexes. Each structure comprises a [M (L)]2+ core. The kinetic of complex formation of 2 was investigated and the results are investigated and compare with that of 4. The study showed in general, the formation of 2 and 4 in one phase with a first-order type reaction. Antibacterial activities of all the prepared compounds against some pathogenic bacteria (Staphylococcus aureus and Escherichia coli) were evaluated, which exhibit a good growth inhibitory activity.